Ephaptic Coupling of Cortical Neurons: Possible Contribution of Astroglial Magnetic Fields?. (1st February 2018) - Martinez-Banaclocha, Marcos
Graphical abstract: Highlights: To review the current knowledge supporting the contribution of neurons and astrocytes on ephaptic neuronal modulation. To suggest that astroglial magnetic fields associated with Ca 2+ waves may play a role in the ephaptic coupling of neurons. To propose that the ultrastructural organization of the mammalian neocortex is appropriated for bio-magnetic interactions. Abstract: The close anatomical and functional relationship between neuronal circuits and the astroglial network in the neocortex has been demonstrated at several organization levels supporting the idea that neuron-astroglial crosstalk can play a key role in information processing. In addition to chemical and electrical neurotransmission, other non-synaptic mechanisms called ephaptic interactions seem to be important to understand neuronal coupling and cognitive functions. Recent interest in this issue comes from the fact that extra-cranial electric and magnetic field stimulations have shown therapeutic actions in the clinical practice. The present paper reviews the current knowledge regarding the ephaptic effects in mammalian neocortex and proposes that astroglial bio-magnetic fields associated with Ca 2+ transients could be implicated in the ephaptic coupling of neurons by a direct magnetic modulation of the intercellular local field potentials.